Analisis Perbandingan Regulasi Prinsip Corporate Social Responsibility (CSR) Antar Negara Indonesia dan India - Mohamad Imam Tanthowy (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
Corporate Social Responsibility (CSR) has evolved from a voluntary initiative into a legal obligation in many countries, including Indonesia and India. This study aims to analyze and compare the CSR regulations between the two countries, focusing on legal foundations, scope of implementation, corporate obligations, and the effectiveness of enforcement. In Indonesia, CSR is regulated under Law No. 40 of 2007 on Limited Liability Companies and Law No. 25 of 2007 on Capital Investment, which mandate companies operating in the natural resource sector to carry out social and environmental responsibilities. Meanwhile, in India, CSR obligations are more broadly applied through the Companies Act 2013, which requires companies meeting specific financial criteria to allocate at least 2% of their average net profits towards CSR activities. The results of this study indicate that CSR regulation in India is more structured and comprehensive compared to Indonesia, particularly in terms of reporting mechanisms, monitoring, and legal sanctions. This comparison provides valuable insight for developing a more effective and equitable CSR regulatory model that benefits society, corporations, and the state.